Genome surgery using Cas9 ribonucleoproteins for the treatment of age-related macular degeneration - Kim, Kyoungmi (Genome Res, 2017)
RNA-guided genome surgery using CRISPR-Cas9 nucleases has shown promise for the treatment of diverse genetic diseases. Yet, the potential of such nucleases for therapeutic applications in nongenetic diseases is largely unexplored. Here, we focus on age-related macular degeneration (AMD), a leading cause of blindness in adults, which is associated with retinal overexpression of, rather than mutations in, the VEGFA gene. Subretinal injection of preassembled, Vegfa gene–specific Cas9 ribonucleoproteins (RNPs) into the adult mouse eye gave rise to mutagenesis at the target site in the retinal pigment epithelium. Furthermore, Cas9 RNPs effectively reduced the area of laser-induced choroidal neovascularization (CNV) in a mouse model of AMD. Genome-wide profiling of Cas9 off-target effects via Digenome-seq showed that off-target mutations were rarely induced in the human genome. Because Cas9 RNPs can function immediately after in vivo delivery and are rapidly degraded by endogenous proteases, their activities are unlikely to be hampered by antibody- and cell-mediated adaptive immune systems. Our results demonstrate that in vivo genome editing with Cas9 RNPs has the potential for the local treatment for nongenetic degenerative diseases, expanding the scope of RNA-guided genome surgery to a new dimension.